Making a new democracy work: the role of civil society organisations (CSOs) in combating corruption during democratic transition in Indonesia - Setiyono, Budi (Curtin University, 2010)
Corruption has often stimulated the collapse of authoritarian regimes and was followed by democratisation in a number of developing countries. Many new democratic regimes, however, have also been failed to control corruption because during the transition to democracy, their institutional structure of governance has typically not functioned well. In Indonesia too, corruption has been a highly pertinent issue that has both stimulated and compromised the regime‘s transition to democracy. This has provided a platform for civil society organisations (CSOs) to take an active political role. Yet insufficient empirical examination exists on the role of CSOs in combating corruption during democratic transition and the implication for democratisation.This thesis documents and critically examines the contribution of CSOs (more specifically anti-corruption CSOs) in Indonesia, an examination essential to the study of democratisation and anti-corruption efforts. It investigates how and to what extent CSOs can fight corruption during democratic transition. Owing to the ineffectiveness and unwillingness of the state, civil associations have undertaken initiatives in fighting and underscoring corruption into the domain of public debate. They work at two levels of battle: strategic and practical. At the strategic level, CSOs have contributed to the creation of the legal and institutional frameworks necessary for eradicating corruption. Many of their advocacies have brought about the creation of anti-corruption regulations and supervisory bodies to combat corruption. At the practical level, CSOs have organised social monitoring to call state officials to account. It has been CSOs that have mobilised the public to take civic action against corruption. By successfully taking a number of government officials and politicians to court, CSOs have also enhanced the legal system against corruption.Given the significance of the contribution of CSOs, this thesis argues that they have a real nascent force to advance democratisation: not only because the anti-corruption movement that they initiated has been instrumental in shaping political transformation, but they have also opened channels between the state and civil society that work as a system of accountability, part of a long-term project of establishing a democratic principle rooted in grassroots participation.This thesis argues, however, that despite their important role, the activities of CSOs have not been perfect and, accordingly, should not be interpreted as a panacea for all problems of corruption and democratisation. Therefore, it should be a concern for all the stakeholders involved – including the government, donor agencies, and the general public – to enhance the capacity of CSOs.